PENGARUH MODEL PEMBELAJARAN SIMULASI TERHADAP HASIL BELAJAR EKONOMI PESERTA DIDIK KELAS X SEMESTER GENAP SMA GAJAH MADA BANDAR LAMPUNG TAHUN PELAJARAN 2018/2019 - Andini, Dwi; RB, Muhammad; Meladi, Melado (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2020)
The problem in this study seen from the identification of problems is the economic learning outcomes of students are still low, lack of interest and motivation of students in economics. This study aims to determine the effect of the use of learning models Simulation on learning outcomes of students in Economics subjects. The researcher used the experimental method as for the population in this study were the tenth grade students of Gajah Mada High School, Bandar Lampung, the sample consisted of two classes namely X1 and X2, where class X1 as the Experimental class used 36 simulation learning models and class X2 as the control class using conventional methods in the form of lectures with the number of students 36. The instruments used are in the form of multiple choices. The results of testing the hypotheses that have been done are obtained ttes = 4.70 and from the distribution table t at the 5% significance level it is known tt (1-0.5 Î±) = 2.00 so that it can be concluded that there are differences in learning outcomes using influential Simulation learning models positive for student economic learning outcomes compared to Conventional learning models